RECENT DEVELOPMENTS IN ACCOUNTING THEORY AND PRACTICE. - Funk, Roland W. (The Accounting Review, 1950)
A critical analysis of practice is not the only basis for a good theory. Nor must theory be completely applied to a practical situation in order for it to be considered good theory. A body of thought which may be developed from accounting practice and which is logical in all respects may be said to be derived largely from practice. But it must be compatible with the purposes of accounting and it must not be in controversy to other aspects of accounting. "Developments" in accounting theory and practice refer, primarily, to the degree to which accounting theory and practice is disclosed and applied. Perhaps it is more important to consider such developments as referring to the application to practice of latent theory, the discarding or revision of old theory, or the evolution of new theory. In any case, the existing theory would be available for continued application in practical situations to the extent considered appropriate.